Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Bahasa Indonesia Materi Menelaah Unsur Pembangun Teks Puisi Melalui Model Discovery Learning di Kelas VIII SMP Negeri 19 Kota Bogor - Ruchyati, Ida (Journal of Social Studies Arts and Humanities (JSSAH), 2023)
IMPROVING STUDENT LEARNING OUTCOMES IN INDONESIAN SUBJECT MATERIAL EXAMINING THE BUILDING ELEMENTS OF POETRY TEXTS THROUGH THE DISCOVERY LEARNING MODEL IN GRADE VIII JUNIOR HIGH SCHOOLS (SMP NEGERI 19 KOTA BOGOR) The purpose of this study was to determine the increase in student learning outcomes regarding the material Examining the Building Elements of Poetry Texts in Indonesian subjects in class VIII Junior High School through the use of the Discovery Learning Learning Model. The method used is a class action research method consisting of two cycles. In the first cycle, learning is carried out using the Discovery Learning Learning Model, while in the second cycle using the Discovery Learning Learning Model which has been refined. In each cycle consists of four stages of research namely planning, implementation of action, observation, and reflection. The research data were analyzed using a comparative descriptive followed by reflection. Comparative descriptive is done by comparing the initial condition data, cycle 1 and cycle 2, both for learning outcomes. The results of this study indicate that: First, the use of the Problem Based Learning Learning Model can improve student learning outcomes. It is proven that the percentage of student learning outcomes has increased from the initial condition of the average daily test score of 66.79 in cycle I to 75.67 and in cycle II to 82.91, or in the final condition it has increased by 24.14% from the condition beginning. It is proven that the percentage of students' learning completeness increased from the initial conditions in cycle I to 60.61% in cycle II to 84.85 or in the final conditions an increase of 40% from the initial conditions.